The (re)makings of art history and Europe after 1945 - Haro García, Noemi de; Mayayo, Patricia; Carrillo Castillo, Jesús Ma. 1966- (2020)
This introduction presents an overview of the key concepts discussed in the subsequent chapters of this book. The book examines the intermeshing of state power and art history in European countries since the end of the Second World War and up to the present. It discusses specific case studies with the aim of starting to draw the spectrum of the role played by art and art historical discourses in legitimising totalitarian regimes as well as their place within the new symbolic order created during and after the transitions to democracy. The book demonstrates that the making of art history since 1945 has also involved coming to terms with notions lying at the core of the discipline. It explores the renewed interest of art historical scholarship in the study of the different forms adopted by the ‘medium’ of the exhibition.
Keywords: Geschichte 1945-1989; Ost-West-Konflikt; Kunstgeschichte -- Fach; Demokratie; Staatsgewalt; Totalitarismus; Kulturpolitik; Kunstgeschichtsschreibung; Europa